Post-eastern Mediterranean Transient Oxygen Decline in the Deep Waters of the Southeast Mediterranean Sea Supports Weakening of Ventilation Rates - Sisma-Ventura, Guy; Kress, Nurit; Silverman, Jacob; Gertner, Yaron; Ozer, Tal; Biton, Eli; Lazar, Ayah; Gertman, Isaac; Rahav, Eyal; Herut, Barak (Frontiers in Marine Science, 2021)
Long-term trends in oxygen, salinity, and nutrients were followed in the Southeastern Mediterranean (SEMS) deep waters from 2002 to 2020. Results show a net decrease in oxygen since 2008 of −0.5 ± 0.1 μmol kg−1 yr−1 in the bathypelagic depths (1,200–2,000 m). Multiannual variability in oxygen levels superimposed this trend, and is likely associated with variations in thermohaline fluxes. The 2020 mean oxygen concentration of 179.5 ± 2.3 μmol kg−1 is comparable to the pre-Eastern Mediterranean Transient (EMT) mean value. The post-EMT signature is clearly demonstrated in both oxygen and salinity over the period of 2002–2013, but since 2014 it diminished, mainly due to mixing of the Aegean deep water (AegDW) mass with the overlying old Adriatic water mass. This trend reflects a switch back to the pre-EMT regime, characterized by thermohaline homogeneity of the deep water column in the SEMS. The long-term decline of deep water oxygen levels is also accompanied by a corresponding increase in dissolved inorganic nutrients, supporting aging of the deep water masses. Our results suggest that ventilation of the SEMS deep water is currently occurring at a lower, pre-EMT rate, probably as a result of moderated deep water formation in recent time.